Communication between endothelial cells and osteoblasts in regulation of bone homeostasis: Notch players - Daria Perepletchikova; Anna Malashicheva (Stem Cell Research & Therapy)
Abstract Endothelial cells coat blood vessels and release molecular signals to affect the fate of other cells. Endothelial cells can adjust their behavior in response to the changing microenvironmental conditions. During bone regeneration, bone tissue cells release factors that promote blood vessel growth. Notch is a key signaling that regulates cell fate decisions in many tissues and plays an important role in bone tissue development and homeostasis. Understanding the interplay between angiogenesis and osteogenesis is currently a focus of research efforts in order to facilitate and improve osteogenesis when needed. Our review explores the cellular and molecular mechanisms including Notch-dependent endothelial-MSC communication that drive osteogenesis-angiogenesis processes and their effects on bone remodeling and repair.